Activation of the human immunodeficiency virus type 1 long terminal repeat by vaccinia virus. - Stellrecht, K A (1992)
A variety of DNA viruses are known to activate gene expression directed by the long terminal repeat (LTR) of human immunodeficiency virus type 1 (HIV-1). In light of the proposed use of recombinant vaccinia virus for HIV-1 vaccines, evaluation of the role of vaccinia virus in HIV-1 activation is warranted. To investigate whether vaccinia virus induces HIV LTR-directed gene expression, transient expression assays in Jurkat cells persistently infected with vaccinia virus (Jvac) using plasmid DNA containing the LTR linked to the bacterial chloramphenicol acetyltransferase (CAT) gene were performed. CAT activity in Jvac cells was always recorded, although the level appears to fluctuate independently of virus titers. Dual intracytoplasmic staining and fluorescence-activated cell sorter analysis showed that CAT activity was expressed in the infected cells. CAT expression was not due to plasmid replication, since plasmid DNA extracted from Jvac cells 48 h after transfection was restricted only by enzymes which recognize methylated sequences, indicating a prokaryotic source for the DNA. These findings suggest that a factor(s) present in vaccinia virus-infected cells is capable of activating the LTR of HIV-1.